A systematic review on peripheral blood-derived mesenchymal stem cells as a therapy for cartilage repair - Rufaidah Othman,; Chong, Pan Pan; Nahrizul Adib Kadri,; Tunku Kamarul, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Comprehensive analysis showed that the popularity of research peripheral blood-derived mesenchymal stem cells for knee cartilage repair is still lacking, as they peripherally exist at a very low level. Despite its small cell number, peripheral blood is yet one of the most convenient sources of mesenchymal stem cells due to its less invasive method to harvest. This study aimed to systematically review the current evidence of peripheral blood-derived mesenchymal stem cells towards the repair of articular cartilage defect. A comprehensive literature search was performed to identify all in vivo studies reporting the structural outcome of articular cartilage repair in the knee following electronic databases: PubMed, WOS and SCOPUS. The in vitro characterizations of peripheral blood-derived mesenchymal stem cells were evaluated to enable quality assessment. Literature from 1934 to 2019 showed 4822 of total articles with only three findings related to pre-clinical studies were included in the analysis. The selection of animal model, type of transplantation, mobilization of the peripheral blood, in vitro culture condition, type of scaffold, assessments on the cartilage defect, and the outcome measures were heterogeneous. Evidence showed that mobilized peripheral blood-derived mesenchymal stem cells were more superior in repairing articular cartilage compared to those that were non-mobilized. These cells also showed a comparable capability in repairing articular cartilage than the commonly used bone marrow mesenchymal stem cells. Overall, more progress is needed to expand the usage of peripheral blood-derived mesenchymal stem cells from basic biological science to the translational studies in clinical practice.